Immunometabolism in the Aging Heart - Kranti A. Mapuskar; Barry London; Zeb R. Zacharias; Jon C.D. Houtman; Bryan G. Allen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Structural, functional, and molecular‐level changes in the aging heart are influenced by a dynamic interplay between immune signaling and cellular metabolism that is referred to as immunometabolism. This review explores the crosstalk between cellular metabolic pathways including glycolysis, oxidative phosphorylation, fatty acid metabolism, and the immune processes that govern cardiac aging. With a rapidly aging population that coincides with increased cardiovascular risk and cancer incidence rates, understanding the immunometabolic underpinnings of cardiac aging provides a foundation for identifying therapeutic targets to mitigate cardiac dysfunction. Aging alters the immune environment of the heart by concomitantly driving the changes in immune cell metabolism, mitochondrial dysfunction, and redox signaling. Shifts in these metabolic pathways exacerbate inflammation and impair tissue repair, creating a vicious cycle that accelerates cardiac functional decline. Treatment with cancer therapy further complicates this landscape, as aging‐associated immunometabolic disruptions augment the susceptibility to cardiotoxicity. The current review highlights therapeutic strategies that target the immunometabolic axis to alleviate cardiac aging pathologies. Interventions include modulating metabolic intermediates, improving mitochondrial function, and leveraging immune signaling pathways to restore cardiac health. Advances in immunometabolism thus hold significant potential for translating preclinical findings into therapies that improve the quality of life for the aging population and underscore the need for approaches that address the immunometabolic mechanisms of cardiac aging, providing a framework for future research.